Production potential and monetary advantage of winter maize (Zea mays) -based intercropping systems under irrigated conditions in central Uttar Pradesh - TRIPATHI, A K; KUMAR, ANAND; NATH, SOMENDRA (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was carried out during winter (rabi) seasons of 2003–04 and 2004–05 at Kanpur to find out the production potential and economic viability of winter maize (Zea mays L.) intercropped with potato (Solanum tuberosum L.), Indian mustard [Brassica juncea (L.) Czernj. & Cosson], toria (Brassica campestris var. toria), pea (Pisum sativum L. sensulato), linseed (Linum usitatissimum L.) and wheat (Triticum aestivum L. emend. Fiori & Paol.) for central plain zone of Uttar Pradesh. Values of land equivalent ratio (LER) and area-time equivalent ratio (ATER) with all the intercropping systems were greater indicating advantage in yield, land-use efficiency and monetary return/unit time and space over the respective monocultures. All the intercrops with maize recorded significantly higher maize-equivalent yield than the sole crop. Intercropping of maize with potato was more advantageous than the other intercrops. Maize + potato appeared to be biologically the most efficient and economically viable system giving the highest maize grain yield (6 091 kg/ha), maize-equivalent yield (13 792 kg/ha), production efficiency (276.1%), land equivalent ratio (2.14), area-time equivalent ratio (1.91), monetary advantage (Rs 39 017) and net realization (Rs 32 369/ha), followed by maize + pea. Indian mustard, toria and wheat were found non-compatible with winter maize.